Integration of Remote Vehicle Tracking System Location using GSM Modem and Web Mapping Service Application - Ahmad Fuad, Muhammad Ridhwan (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
In Malaysia, vehicles theft cases keep increasing from days to days and the recovery rate of the stolen vehicle is very minimal. Some of service provider companies in Malaysia lack of fleet management which could cause decrease in efficiency of the services or reduce their profit as the manager or owner of the company could not monitor any transportation activities related to the companies. Remote Vehicle Tracking System could overcome or become a solution to those problems. This project is about the integration of Remote Vehicle Tracking System location using the GSM (Global System for Mobile Communication) Modem with Google Map. This project will deal with SMS (Short Message Service) enabled vehicle tracking system. The GSM modem will receive the coordinates through SMS send by transmitter (in this project, the transmitter which will act as location information sender will be simulated by using a mobile phone) and updates the location information into a database. The information then will be parsed to a preferred website (online/local-host) and the position of the vehicle will be displayed through a Google Maps application. The core of this project is the integration of the GSM modem which will act as a location information receiver and the Google Maps itself. A website will be developed to aid the user to track and view the vehicles location easily. The website will display the vehicle location through the Google Map and can be access anywhere as long as Internet connection is available. To improvise and add more functionality to the project, more functions regarding this project was added. There are three working functions for this project which are Display the Latest Tracked Vehicle Location, Display the Route History of Tracked Vehicle, lastly, Route and Destination Planner Base on Current Location.